Fracture behaviour of bamboo fiber reinforced epoxy composites. (1st May 2017) - Khan, Ziaullah; Yousif, B.F.; Islam, Mainul
Abstract: In this work, experimental and numerical study on fracture behaviour of bamboo fiber reinforced epoxy composites is presented. Optimum NaOH concentration for treatment of bamboo fibers was determined through single fiber tensile test and microscopic inspection of fiber surface through SEM (Scanning Electron Microscopy). The results demonstrated that 6% NaOH treated fibers showed maximum ultimate tensile strength of 234 MPa. Single fiber fragmentation test results showed that interfacial adhesion is improved by treating fibers with 6% NaOH. Bamboo fiber reinforced epoxy composite was fabricated using 6% NaOH treated bamboo fibers of length 10 mm, 20 mm and 25 mm with random distribution in epoxy matrix. Mode-I plane strain fracture toughness (KIC ) of bamboo fiber reinforced epoxy composites was investigated based on Linear Elastic Fracture Mechanics (LEFM) approach as per ASTMD5045 . Results showed that composites having 25 mm length of fibers had the largest KIC value of 2.67 MPa.m 1/2, whereas composites with 10 mm fiber length showed lowest value of fracture toughness KIC of 1.61 MPa.m 1/2 . SEM results revealed that fiber breakage, matrix cracking, fiber matrix debonding and fiber pull out are major causes of failure of composite. Simulation/modelling of crack propagation in CT (Compact Tension) specimen by using FEA software ABAQUS ® showed similar results as experimental values. Graphical abstract: Highlights: Optimum concentration of NaOH for treatment of bamboo fibres is 6%. Bamboo epoxy composite having 25mm fibre length has more (KIC ) value than composites with smaller fibre lengths. Matrix cracking, fibre pull out and fibre breakage are significant causes of composite failure during fracture test. FEA simulation using ABAQUS shows similar results as experimental work for fracture toughness of bamboo epoxy composite.